2017
DOI: 10.1002/aoc.4115
|View full text |Cite
|
Sign up to set email alerts
|

Novel organometallic chalcones functionalized with a crown ether fragment as optical ion chemosensors

Abstract: We previously reported the synthesis and characterization of new organometallic chalcones derived from ferrocene, cyrhetrene and cymantrene functionalized with a benzo‐15‐crown‐5 fragment. The ferrocene and cyrhetrene chalcones have been investigated as chemosensors for metal ions with optical response in acetonitrile. Several metal ions were selected considering the diameter of the cavity and the charge‐to‐radius ratio of the cation. The stoichiometry of the complexes was determined using Job's method. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…According to Job's plot, the binding stoichiometry between BTC and Fe 3+ was 1:1, and the fluorescence intensity peaked at a mole fraction of 0.5 ( Figure S8 , ESI). Fluorescence titration by the Benesi‐Hildebrand equation can be used to estimate the association constant between BTC and Fe 3+ [25]. 1normalII0goodbreak=1ImaxI0goodbreak+1)(Imaxgoodbreak−I0][Fe3+Ka$$ \frac{1}{\mathrm{I}-{\mathrm{I}}_0}=\frac{1}{{\mathrm{I}}_{\mathrm{max}}-{\mathrm{I}}_0}+\frac{1}{\left({\mathrm{I}}_{\mathrm{max}}-{\mathrm{I}}_0\right)\left[{\mathrm{Fe}}^{3+}\right]{\mathrm{K}}_{\mathrm{a}}} $$ …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Job's plot, the binding stoichiometry between BTC and Fe 3+ was 1:1, and the fluorescence intensity peaked at a mole fraction of 0.5 ( Figure S8 , ESI). Fluorescence titration by the Benesi‐Hildebrand equation can be used to estimate the association constant between BTC and Fe 3+ [25]. 1normalII0goodbreak=1ImaxI0goodbreak+1)(Imaxgoodbreak−I0][Fe3+Ka$$ \frac{1}{\mathrm{I}-{\mathrm{I}}_0}=\frac{1}{{\mathrm{I}}_{\mathrm{max}}-{\mathrm{I}}_0}+\frac{1}{\left({\mathrm{I}}_{\mathrm{max}}-{\mathrm{I}}_0\right)\left[{\mathrm{Fe}}^{3+}\right]{\mathrm{K}}_{\mathrm{a}}} $$ …”
Section: Resultsmentioning
confidence: 99%
“…Job plot analysis was performed to determine the precise stoichiometry of the metal ion with the probe BTC [58]. We plotted the rela- Benesi-Hildebrand equation can be used to estimate the association constant between BTC and Fe 3+ [25].…”
Section: Fe 3+ Metal Ion Sensing Studymentioning
confidence: 99%
See 1 more Smart Citation
“…14 Also, organometallic chalcones have commanded interest as optical chemosensors in the field of metal ion recognition. 15,16 Notwithstanding the considerable interest on the biological activity of the chalcones, there has been a great paucity of mechanistic information on these compound photoredox reactions. In this context, some photochemical processes related to organic chalcones have been described previously in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Another example is a group of chalcones substituted with methylsulfonyl or trifluoromethyl moieties, which have been tested for their inhibitory activities on monoamine oxidase-B. , In the same context, organometallic chalcones have shown activity against some diseases; e.g., ferrocenyl–cymantrenyl heterobimetallic chalcones exhibit moderate antimalarial and antibacterial activities, while mononuclear cyrhetrenyl chalcones have shown to be active when tested in the evaluation of in vitro antimalarial activity . Also, organometallic chalcones have commanded interest as optical chemosensors in the field of metal ion recognition. , Notwithstanding the considerable interest on the biological activity of the chalcones, there has been a great paucity of mechanistic information on these compound photoredox reactions. In this context, some photochemical processes related to organic chalcones have been described previously in the literature. , Several authors have reported the photoinduced trans–cis isomerization of hydroxy-chalcones, in homogeneous and heterogeneous media, followed by a tautomerization reaction, which occurs in acid media. , Other photophysical processes related to organic chalcones have been identified using the flash photolysis technique, such as photoinduced proton transfer and triplet excited-state formation in a water–ethanol mixture .…”
Section: Introductionmentioning
confidence: 99%